Evaluation of Minimally Invasive Vertical Extraction Technique of Crowded Lower Incisors: A Case Series Study - Saeed Hameed Tutmayi (Erbil Dental Journal)
Background and Objective: Innovations in tooth extraction techniques and instruments have evolved over time to minimize trauma to surrounding tissues. In severely crowded cases, extracting anterior teeth poses a challenge for surgeons due to the risk of traumatizing adjacent teeth and surrounding hard and soft tissues. This study aims to evaluate the applicability and popularization of a novel a traumatic vertical extraction technique, known as minimally invasive vertical extraction of lower anterior teeth.